Management Planning for Nature Conservation : theoretical basis & practical guide - Alexander, Mike. (Springer Netherlands, 2017)
Mike Alexander’s Management Planning for Nature Conservation brings a new dimension to the modern literature on conservation management. Combining key theories with real practice it fills a critical gap which has often hindered in-depth understanding of the planning process. The book provides historical and rational background which helps to explain what makes a really effective management plan, and it presents a detailed practical guide to developing such a plan. It concludes with a series of case studies which clearly illustrate the underlying principles drawn out in the text, while highlighting the different approaches demanded by very different sites.